Abnormal interaction of VDAC1 with amyloid beta and phosphorylated tau causes mitochondrial dysfunction in Alzheimer's disease - Manczak, Maria; Reddy, P Hemachandra (Human molecular genetics, 2012)
The purpose of our study was to determine the relationship between voltage-dependent anion channel 1 protein (VDAC1) and amyloid beta (Aβ) and phosphorylated tau in Alzheimer's disease (AD). Using brain specimens from AD patients, control subjects and 6-, 12- and 24-month-old Aβ precursor protein (APP) transgenic mice, we studied VDAC1 protein levels. Further, we also studied the interaction between VDAC1 and Aβ (monomers and oligomers) and phosphorylated tau, using cortical issues from AD patients, control subjects, APP, APP/PS1 and 3XTg.AD mice. We also studied age- and VDAC1-linked, mutant APP/Aβ-induced mitochondrial dysfunction in APP and non-transgenic wild-type (WT) mice. We found progressively increased levels of VDAC1 in the cortical tissues from the brains of patients with AD, relative to control subjects, and significantly increased levels of VDAC1 in the cerebral cortices of 6-, 12- and 24-month-old APP transgenic mice, relative to the age-matched control WT mice. Interestingly, we found VDAC1 interacted with Aβ and phosphorylated tau in the brains from AD patients and from APP, APP/PS1 and 3XTg.AD mice. We found progressively increased mitochondrial dysfunction in APP mice relative to WT mice. These observations led us to conclude that VDAC1 interacts with Aβ, and phosphorylated tau may in turn block mitochondrial pores, leading to mitochondrial dysfunction in AD pathogenesis. Based on current study observations, we propose that reduced levels of VDAC1, Aβ and phosphorylated tau may reduce the abnormal interaction between VDAC1 and APP, VDAC1 and Aβ, and VDAC1 and phosphorylated tau; and that reduced levels of VDAC1, Aβ and phosphorylated tau may maintain normal mitochondrial pore opening and pore closure, ultimately leading to normal mitochondrial function, mitochondria supplying ATP to nerve terminals and boosting synaptic and cognitive function in AD.